Pyrucularia grisea en alpiste (Phalaris canariensis L.) en Argentina - Pedraza, Maria Virginia; Liberman, Claudia Alejandra; Cattaneo, Fernando Daniel; Asselborn, Miriam (Asociación Argentina de Fitopatólogos, 2021)
Póster